FEDOR DOSTOEVSKII IN BRITAIN: THE TALE OF AN UNTALENTED GENIUS. - Aiello, Lucia (Modern Language Review, 2003)
Discusses the persisting mistrust of author Fedor Dostoevskii's artistic abilities. General presentation of Dostoevskii as a genius, whose talent resided in something other than his artistic accomplishments; Characterization of the genius without talent; Development of the modern concept of 'genius'; Impossibility of inscribing Dostoevskii's works within the traditional parameters of the novelistic genre.